2018
DOI: 10.1111/fme.12322
|View full text |Cite
|
Sign up to set email alerts
|

Post‐release predation mortality of age‐0 hatchery‐reared Chinook salmon from non‐native smallmouth bass in the Snake River

Abstract: Release of age‐0 hatchery‐reared fall Chinook salmon, Oncorhynchus tshawytscha (Walbaum), in the Snake River resulted in up to 30‐fold increases in salmon consumption by non‐native smallmouth bass, Micropterus dolomieu Lacepѐde. In an upper river reach, smallmouth bass fed intensively during a release in May, but Chinook salmon consumption returned to pre‐release levels within 1–2 days as hatchery‐reared fish quickly emigrated downstream. The predation response during a June release located farther downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Smallmouth bass were collected from 2013 to 2018 to describe diet changes and estimate subyearling loss to predation in each reach, but not all reaches were sampled every year. Data for this study were collected and combined with data from previously published studies (Erhardt et al 2018a ; Erhardt and Tiffan 2018 ) to derive monthly estimates of predation metrics for each study reach. Study designs varied between reaches because of potential differences in habitat-related sampling efficiencies, safety, and logistical reasons (e.g., limited access points within Hells Canyon).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Smallmouth bass were collected from 2013 to 2018 to describe diet changes and estimate subyearling loss to predation in each reach, but not all reaches were sampled every year. Data for this study were collected and combined with data from previously published studies (Erhardt et al 2018a ; Erhardt and Tiffan 2018 ) to derive monthly estimates of predation metrics for each study reach. Study designs varied between reaches because of potential differences in habitat-related sampling efficiencies, safety, and logistical reasons (e.g., limited access points within Hells Canyon).…”
Section: Methodsmentioning
confidence: 99%
“…Most sites covered multiple habitat types (i.e., pool, riffle, glide, fan, bar), and sampling occurred on both banks of the river. The start and end points of each site typically occurred at habitat breaks (see Erhardt and Tiffan 2018 for details on habitat delineation) and when possible extended between two rapids. Preliminary analyses showed that the proportions of habitat surveyed in the fixed sampling sites, along with smallmouth bass relative abundances, were representative of the entire reach.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations